Comparative Genomics of 86 Whole-Genome Sequences in the Six Species of the Elizabethkingia Genus Reveals Intraspecific and Interspecific Divergence - Liang, Chih-Yu (Sci Rep, 2019)
Bacteria of the genus Elizabethkingia are emerging infectious agents that can cause infection in humans. The number of published whole-genome sequences of Elizabethkingia is rapidly increasing. In this study, we used comparative genomics to investigate the genomes of the six species in the Elizabethkingia genus, namely E. meningoseptica, E. anophelis, E. miricola, E. bruuniana, E. ursingii, and E. occulta. In silico DNA–DNA hybridization, whole-genome sequence-based phylogeny, pan genome analysis, and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed, and clusters of orthologous groups were evaluated. Of the 86 whole-genome sequences available in GenBank, 21 were complete genome sequences and 65 were shotgun sequences. In silico DNA–DNA hybridization clearly delineated the six Elizabethkingia species. Phylogenetic analysis confirmed that E. bruuniana, E. ursingii, and E. occulta were closer to E. miricola than to E. meningoseptica and E. anophelis. A total of 2,609 clusters of orthologous groups were identified among the six type strains of the Elizabethkingia genus. Metabolism-related clusters of orthologous groups accounted for the majority of gene families in KEGG analysis. New genes were identified that substantially increased the total repertoire of the pan genome after the addition of 86 Elizabethkingia genomes, which suggests that Elizabethkingia has shown adaptive evolution to environmental change. This study presents a comparative genomic analysis of Elizabethkingia, and the results of this study provide knowledge that facilitates a better understanding of this microorganism.